Role of Pharmacists during and Post COVID-19 Pandemic-An Indian Perspective - Dey, Anuradha; Das, Shreya; Singhvi, Gautam; Shrivastava, Richa (Journal of Pharmacy Practice and Community Medicine)
The multiple outbreaks of COVID-19 have led to a public health crisis, affecting millions across the globe. The healthcare fraternity is shouldering a huge responsibility and is working tirelessly to curb the spread of the disease. These unprecedented times demand that the usual roles of pharmacists be modified. Pharmacists have to rise up to the challenges and strategize accordingly. Many nations are trying to tackle the repercussions of the second wave of COVID-19 and the latest third wave by OMICRON variant, which has punctured the healthcare system and led to question the resource management and governance failures that have affected thousands of lives. It is difficult to bring the situation under control in several places, predominantly middle and lowincome countries. Thus, to succeed in providing all the healthcare services, changes pertaining to operations, supply management, safety precautions, spreading awareness, vaccination drives, etc., must be incorporated by healthcare workers, especially the pharmacists, to create a maximum positive change. This article highlights the roles and responsibilities of the pharmacists that they can fulfil during and post this pandemic. It also reviews the nature of their functioning, the roles that they can adapt, and identifies places wherein their roles can be expanded or modified in accordance with the countryspecific guidelines.
Keywords: COVID-19; Pandemic; Pharmacist; Community health; Patient care